The Regulator PltZ Regulates a Putative ABC Transporter System PltIJKNOP of Pseudomonas aeruginosa ATCC 27853 in Response to the Antimicrobial 2,4-Diacetylphloroglucinol - Guo, Ding-Ding; Luo, Li-Ming; Ma, Hai-Long; Zhang, Si-Ping; Xu, Hang; Zhang, Honghua; Wang, Yong; Yuan, Yongna; Wang, Zhen; He, Yong-Xing (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa is an opportunistic pathogen commonly infecting immunocompromised patients with diseases like cystic fibrosis (CF) and cancers and has high rates of recurrence and mortality. The treatment efficacy can be significantly worsened by the multidrug resistance (MDR) of P. aeruginosa, and there is increasing evidence showing that it is easy for this pathogen to develop MDR. Here, we identified a gene cluster, pltZ-pltIJKNOP, which was originally assumed to be involved in the biosynthesis of an antimicrobial pyoluteorin, significantly contributing to the antibiotic resistance of P. aeruginosa ATCC 27853. Moreover, the TetR family regulator PltZ binds to a semi-palindromic sequence in the promoter region of the pltIJKNOP operon and recognizes the antimicrobial 2,4-diacetylphloroglucinol (2,4-DAPG), which in turn induces the expression of the pltIJKNOP operon. Using quantitative proteomics method, it was indicated that the regulator PltZ also plays an important role in maintaining metabolic hemostasis by regulating the transporting systems of amino acids, glucose, metal ions, and bacteriocins.